Cosmic-Ray Anisotropies in Right Ascension Measured by the Pierre Auger Observatory - Calcagni, Laura Randa (2020)
We present measurements of the large-scale cosmic-ray anisotropies in right ascension, using data collected by the surface detector array of the Pierre Auger Observatory over more than 14 years. We determine the equatorial dipole component, ~d⊥, through a Fourier analysis in right ascension that includes weights for each event so as to account for the main detector-induced systematic effects. For the energies at which the trigger efficiency of the array is small, the “East-West” method is employed. Besides using the data from the array with detectors separated by 1500 m, we also include data from the smaller but denser sub-array of detectors with 750 m separation, which allows us to extend the analysis down to ∼ 0.03 EeV. The most significant equatorial dipole amplitude obtained is that in the cumulative bin above 8 EeV, d⊥ = 6.0 +1.0 −0.9%, which is inconsistent with isotropy at the 6σ level. In the bins below 8 EeV, we obtain 99% CL upper-bounds on d⊥ at the level of 1 to 3 percent. At energies below 1 EeV, even though the amplitudes are not significant, the phases determined in most of the bins are not far from the right ascension of the Galactic center, at αGC = −94◦ , suggesting a predominantly Galactic origin for anisotropies at these energies. The reconstructed dipole phases in the energy bins above 4 EeV point instead to right ascensions that are almost opposite to the Galactic center one, indicative of an extragalactic cosmic ray origin.